Hierarchical carbon microflowers supported defect-rich Co3S4 nanoparticles: An efficient electrocatalyst for water splitting. (30th April 2020) - Zhu, Xiaojing; Dai, Jiale; Li, Ligui; Zhao, Dengke; Wu, Zexing; Tang, Zhenghua; Ma, Li-Jun; Chen, Shaowei
Abstract: Developing highly efficient and cost-effective bifunctional electrocatalysts for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) represents a judicious way to produce massive hydrogen fuel through electrochemical water splitting. Herein, defect-rich Co3 S4 particles with a diameter less than 5 nm were in-situ grown on nitrogen-doped hierarchical carbon microflowers (Co3 S4 @FNC) through a simple hydrothermal method, in which an unconventional vulcanization process with the strongly coordinating ligand ethylenediamine and formaldehyde serving as structure-directive agents is resorted to effectively control the morphology of catalysts. The resultant Co3 S4 @FNC-Co3 comprises dense Co3 S4 nanoparticles supported on ultrathin nitrogen-doped carbon nanosheets with a thickness of ca. 20 nm, as well as abundant defects on Co3 S4 nanoparticles and highly porous textures on carbon microflowers. These nanostructure merits lead to efficient catalytic activities, featuring a small overpotential of only 250 mV and 140 mV for OER and HER electrocatalysis at 10 mV cm −2 . When Co3 S4 @FNC-Co3 is utilized as a bifunctional catalyst in an alkaline water electrolyzer, a bias of only 1.580 V is able to complement overall water splitting at 10 mA cm −2 . Results in present work may suggest a paradigm in the design and engineering of high-performance electrocatalysts based on nanocomposites of transition metal sulfides and carbons. Graphical abstract: Image 1